Incidence of Forward Head Posture in Mobile Gamers: Cross Sectional Study - Muhammad Ali, Naveeda Ashraf, Sara Khan, Ambreen Zahid, Maria Naeem, Abdul Rehman,Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Forward Head Posture is known as "text neck” or “scholar's neck. FHP is brought about by a number of factors, including prolonged computer and mobile phone usage. Aim: To find out the prevalence of FHP among mobile gamers. Study Design: Cross sectional study. Methodology: Total of 194 participants were considered in this study with age ranging from 18 to30 years. The neck posture was measured using a digital imaging technique. The extent of forward head posture was measured by cervicogenic angle by using landmarks. We drew lines connecting the spinous process of C7 vertebrae to that of the tragus of the ear. Pain was measured by Visual Analog Score while a Goniometer was used to measure ranges of motions of neck. Statistical analysis: The collected data was analyzed by using SPSS version 26. Shapiro-Wilk was used to test normality. Results: Female mobile gamers (55.6%) have the largest percentage of forward head posture, according to the descriptive analysis. Almost 74% of these individuals play for more than 3 hours each day. Pearson correlation test showed positive correlation between the number of hours played and forward head posture having p-value < 0.01. Conclusion: It was concluded that computer players have a higher incidence of forward head posture than other people. Because of anatomical changes, women are more likely to develop FHP.